(untitled) (Zoological Records and Reviews, 2024)
Wildlife in developing regions faces an accelerating suite of human-induced threats that are structurally distinct from those documented in industrialised nations, including subsistence and commercial bushmeat hunting, unregulated small-scale mining, agricultural frontier expansion, live wildlife trade, and zoonotic disease spillover amplified by human-wildlife interface density. This study quantifies the relative importance and spatial distribution of five threat categories across three biodiversity-rich developing regions – West Africa (Ghana, Cameroon), South and Southeast Asia (Cambodia, Myanmar), and Amazonian South America (Peru, Bolivia) – using camera trap surveys (n = 312 stations, 84,621 trap-nights), community interview-based threat perception surveys (n = 1,847 households), NDVI-based deforestation rate analysis, and TRAFFIC wildlife trade seizure data (2018-2023). Deforestation rate was the strongest predictor of large mammal occupancy decline across all three regions (mean beta = -0.68 +- 0.09 per 10% forest cover loss; GLMM p < 0.001). Bushmeat hunting pressure index was negatively correlated with medium and large mammal camera trap rates (r = -0.74, p < 0.001) and showed no significant trend improvement over the five-year study period in West Africa or Southeast Asia. Live wildlife trade seizure data revealed that reptiles and passerine birds constituted 64.8% of confiscated individuals across all three regions. Community surveys identified poverty and lack of livelihood alternatives as the primary drivers of hunting and forest clearing, with 78.4% of households reporting willingness to adopt alternative livelihoods if economically viable options were available. These findings provide a comparative baseline for designing integrated conservation and development interventions aligned with IUCN Category VI protected area management and CITES implementation frameworks.